Case report: A study on the de novo KMT2D variant of Kabuki syndrome with Goodpasture’s syndrome by whole exome sequencing - Li, Shuolin; Liu, Jing; Yuan, Yuan; Lu, Aizhen; Liu, Fang; Sun, Li; Shen, Quanli; Wang, Libo (Frontiers in Pediatrics, 2022)
Kabuki syndrome (KS) is a rare genetic disorder characterized by dysmorphic facial features, skeletal abnormalities and intellectual disability. KMT2D and KDM6A were identified as the main causative genes. To our knowledge, there exists no cases of KS were reported with pneumorrhagia. In this study, a 10-month-old male was diagnosed with KS with typical facial features, skeletal anomalies and serious postnatal growth retardation. Whole exome sequencing of trio family revealed a de novo KMT2D missense variant (c.15143G>A, p. R5048H). The child presented to the pediatric emergency department several times because of cough, hypoxemia and anemia. After doing chest CT and fiberoptic bronchoscopy, we found that the child had pulmonary hemorrhage. During the search for the cause of pulmonary hemorrhage, the patient’s anti-GBM antibodies gradually became positive, and the urine microalbumin level was elevated at the age of 12-month-old. After glucocorticoids and immunosuppressants therapy, the patient became much better. But he had recurrent pulmonary hemorrhage at the age of 16 month. Therefore, the patient underwent digital subtraction angiography (DSA). However, the DSA showed three abnormal bronchial arteries. This single case expands the phenotypes of patients with KS and Goodpasture’s syndrome carried a de novo KMT2D missense variant.